Circular RNA circLDB2 functions as a competing endogenous RNA to suppress development and promote cisplatin sensitivity in non‐squamous non‐small cell lung cancer - Yuanyuan Wang; Luguang Li; Weiyu Zhang; Guojun Zhang (Thoracic Cancer, 2021)
Abstract Background Circular RNAs (circRNAs) are covalently closed RNAs and are implicated in the development of non‐small cell lung cancer (NSCLC). Here, we identified the precise actions of circRNA LIM domain binding 2 (circLDB2, hsa_circ_0069244) in non‐squamous NSCLC development and drug sensitivity. Methods CircLDB2, microRNA (miR)‐346, and LIM and calponin‐homology domains 1 (LIMCH1) were quantified by quantitative real‐time polymerase chain reaction (qRT‐PCR) or western blot. Ribonuclease R (RNase R), actinomycin D, and subcellular localization assays were used to characterize circLDB2. Cell proliferation and viability, colony formation, apoptosis, migration, and invasion were gauged by Cell Counting Kit‐8 (CCK‐8), colony formation, flow cytometry, wound‐healing, and transwell assays, respectively. RNA immunoprecipitation (RIP), RNA pull‐down, and dual‐luciferase reporter assays were used to verify the direct relationship between miR‐346 and circLDB2 or LIMCH1. Animal studies were performed to evaluate the impact of circLDB2 in vivo. Results CircLDB2 was underexpressed in non‐squamous NSCLC and was identified as a bona fide circular transcript. Overexpression of circLDB2 impeded cell proliferation, migration, invasion, and enhanced apoptosis and cisplatin sensitivity in vitro, as well as promoted the antitumor effect of cisplatin in vivo. CircLDB2 regulated cell functional behaviors and cisplatin sensitivity by sponging miR‐346. LIMCH1 was a direct and functional target of miR‐346. Furthermore, circLDB2 acted as a competing endogenous RNA (ceRNA) for miR‐346 to induce LIMCH1 expression. Conclusion Our findings demonstrated that circLDB2 impeded non‐squamous NSCLC development and enhanced cisplatin sensitivity partially by acting as a ceRNA, highlighting circLDB2 as a promising candidate for the development of novel antitumor therapies.